Single-cell sequencing in primary intraocular tumors: understanding heterogeneity, the microenvironment, and drug resistance - He, Lin-feng; Mou, Pei; Yang, Chun-hui; Huang, Cheng; Shen, Ya; Zhang, Jin-di; Wei, Rui-li (Frontiers in Immunology, 2023)
Retinoblastoma (RB) and uveal melanoma (UM) are the most common primary intraocular tumors in children and adults, respectively. Despite continued increases in the likelihood of eyeball salvage due to advancements in local tumor control, prognosis remains poor once metastasis has occurred. Traditional sequencing technology obtains average information from pooled clusters of diverse cells. In contrast, single-cell sequencing (SCS) allows for investigations of tumor biology at the resolution of the individual cell, providing insight into tumor heterogeneity, microenvironmental properties, and cellular genomic mutations. SCS is a powerful tool that can aid in identifying new biomarkers for diagnosis and targeted therapy, which may in turn greatly improve tumor management. In this review, we focus on the application of SCS for evaluating heterogeneity, microenvironmental characteristics, and drug resistance in patients with RB and UM.